Diagnóstico de conservação preventiva de patrimônios arqueológicos: o acervo cerâmico do sítio sambaqui do Tucumã (Melgaço – PA) - CARVALHO, Giovana Pampolha de (2019)
The Archaeological Ceramics is presented very intensely in the Amazon region, representing most of Archaeology collections that are formed here. These goods, of great social importance, sometimes are not stored in spaces such as museums, which are still seen as primarily responsible for the safeguarding of cultural heritage, so we sought the "no museum" as a protective space. We considered then the collected ceramic artifacts on the Tucumã site (Melgaço-Pa), stored in the UFPA Archaeology Laboratory. For the analysis we looked at the medium and microenvironment of the enclosures that safeguard these assets, from Preventive Conservation practices, considering the storage of material, type of handling and environmental factors – relative humidity and temperature variations. In order to examine whether the space store your materials properly.